Antimykobakteriální úcinky pyrrolidinoethylesterů alkoxysubstituovaných fenylkarbamových kyselin - Waisser, K; Cizmárik, J; Drazková, K; Kaustová, J (Ceska a Slovenska farmacie, 2002)
Pyrrolidinoethylesters of alkoxysubstituted phenylcarbamic acids, formerly investigated for local anaesthetic activity, can be considered to be potential antituberculotics. They are effective in vitro against Mycobacterium tuberculosis, Mycobacterium kansasii, and Mycobacterium avium. Their effect increases with the length of the alkyl chain in the alkoxy group bound to the phenyl. The influence of the position of the alkoxyl chain on the phenyl is not too marked, but it seems to decrease in the series m-, p-, o-.
Keywords: karbamáty; antituberkulotika; Mycobacterium; Microbial Sensitivity Tests; Antitubercular Agents; mikrobiální testy citlivosti; Carbamates